STUDI EKSPERIMENTAL TENTANG KEKUATAN DINDING BATA DENGAN PERKUATAN - Pascanawaty, Maya Saridewi; Sukrawa, M; Budiwati, I.A M (JURNAL SPEKTRAN, 2016)
Abstract : Experimental study on the strength of brick walls have been done through literature review and laboratory testing to determine flexural, compressive and shear behaviour of the walls. Four different type of walls were used consisted of walls without plastering (TP), walls with plastering (DP), walls with plastering and chicken mesh reinforcement (DPK), and walls with plastering and wire mesh M4 reinforcement (DPW). The behaviour examined included load-deformation relationship and crack pattern/mode of failure. Laboratory testing included compression test (C) namely CTP, CDP, CDPK and CDPW; bond/shear strength test (S) namely STP, SDP, SDPK, and SDPW; flexural strength tests for failure plane perpendicular to bed joints (F) namely FTP?, FDP?, FDPK?, and FDPW?; and flexural strength tests for failure plane parallel to bed joints, namely FTP//, FDP//, FDPK// and FDPW//. Prior to testing the wall, tests on constituent materials were conducted. Red brick (made in Negara) showed compressive strength of 11,03 N/mm² with water absorption of 21,84%. Compressive strength of mortar was 9,1 N/mm². For the wall specimens testing was done after 28 days. The data obtained from the wall tests showed that compression strength for CTP, CDP, CDPK and CDPW are 3,82 N/mm², 3,84 N/mm², 7,46 N/mm², and 6,33 N/mm², respectively. Values for CDP, CDPK and CDPW are 1,01; 1,95; and 1,86 greater than that for CTP. Bond strength values of STP, SDP, SDPK and SDPW are 0,11 N/mm², 0,28 N/mm², 0,54 N,mm², and 0,42 N/mm², respectively. Values for SDP, SDPK and SDPW are 2,58; 4,88; and 3,87 greater than that of STP. Flexural strength values of FTP? and FDP? are 0,93 N/mm² and 1,27 N/mm², with a failure load for FTP?, FDP?, FDPK?, and FDPW? are sebesar 8,17 KN, 25,17 KN, 31,17 KN and 40,67 KN, respectively. The values for FDP?, FDPK?, and FDPW? are 3,08; 3,82; and 4,98 greater than that of FTP?. Flexural strength values of FTP// and FDP// are 0,38 N/mm² and 0,66 N/mm², with a failure load for FTP//, FDP//, FDPK//, and FDPW// are 3,5 KN, 13,67 KN, 18,33 KN and 32,83 KN, respectively. The values for FDP//, FDPK//, and FDPW// are 3,9; 5,24; and 9,38 greater than that of FTP//. The flexural strength of FDPK and FDPW that’s not analyzed because it was a shear failure and not a flexural failure. Stiffness (EA) for CTP, CDP, CDPK, and CDPW are 725,09 KN, 1096,32 KN,  2357,64 KN, and 1869,78 KN, respectively. The last three values are 1,5; 3,3; and 2,6  greater than that for CTP. Stiffness (EI) of FTP? was 23,78 KNm 2 , while stiffness of FDP?, FDPK? and FDPW? are 68,68 KNm 2 ,  96,31 KNm 2 and 112,17 KNm 2 , respectively, or 2,9; 4,0; and 4,7 greater than that for FTP?. Stiffness (EI) of FTP// was 12,99 KNm 2 , while stiffness of FDP//, FDPK//, and FDPW// were 46,89 KNm 2 , 84,53 KNm 2 and 119,51 KNm 2 , respectively, or 3,6; 6,5; and 9,2 greater than that for FTP//.
Keywords: brick, masonry, compressive strength, bond strength, flexural strength, stiffness